2008
DOI: 10.1016/j.molimm.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Lsc activity is controlled by oligomerization and regulates integrin adhesion

Abstract: Lsc is a hematopoietic-restricted protein that functions as an effector of Gα 12/13-associated G-protein coupled receptors that activates RhoA. In the absence of Lsc leukocytes exhibit impaired migration and B lymphocytes inefficiently resolve integrin-mediated adhesion. Here, we demonstrate that Lsc exists physiologically in primary B lymphocytes as a large molecular weight complex resembling a homo-tetramer. Interfering with the assembly of this large molecular weight Lsc oligomer results in the activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
(115 reference statements)
1
20
0
Order By: Relevance
“…RhoA participates in a number of cell biological processes including regulating cytoskeletal organization, integrin adhesion, and integrin signaling (13). We have previously shown that in B-lymphocytes, Arhgef1 is required for resolving integrin adhesion (14,15), and analyses of Arhgef1-deficient mouse mutants have further demonstrated a requirement for Arhgef1 in leukocyte migration and adhesion (14,16), consistent with the reported role for Arhgef1 in fibroblast adhesion to fibronectin (17).…”
Section: During An Inflammatory Response Resident and Newly Recruitesupporting
confidence: 68%
“…RhoA participates in a number of cell biological processes including regulating cytoskeletal organization, integrin adhesion, and integrin signaling (13). We have previously shown that in B-lymphocytes, Arhgef1 is required for resolving integrin adhesion (14,15), and analyses of Arhgef1-deficient mouse mutants have further demonstrated a requirement for Arhgef1 in leukocyte migration and adhesion (14,16), consistent with the reported role for Arhgef1 in fibroblast adhesion to fibronectin (17).…”
Section: During An Inflammatory Response Resident and Newly Recruitesupporting
confidence: 68%
“…In addition, we used an inducible homodimerization system to show that dimeric (541–605)PRG-FKBP induced actin bundling whereas monomeric (541–605)PRG-FKBP did not. Intriguingly, PRG, and the other RGS-RhoGEFs LARG and p115-RhoGEF, have been shown to exist as dimers, or possibly higher order oligomers, in cells (22, 23, 39, 40). Thus, we can speculate that PRG may affect the structure of the actin cytoskeleton in cells independent of or synergistic with its ability to activate Rho.…”
Section: Discussionmentioning
confidence: 99%
“…Viral supernatants were collected at 48 and 72 hours, and used to infect target cells following standard protocols (Hu et al, 2008). Transduced cells were selected using either cell sorting or antibiotics.…”
Section: Methodsmentioning
confidence: 99%